Bureaucratic Reform and Government Performance Accountability on Local Government Expenditure Efficiency in West Nusa Tenggara - Damar Setiadi; Ryan Setya Budi; Rolan Mart Sasongko; Alvian Alvin Mubarok; Hafidh Rifky Adiyatna (Talent: Journal of Economics and Business, 2026)
This study examines the impact of bureaucratic reform and government performance accountability on local government expenditure efficiency in West Nusa Tenggara Province during 2019–2024. A two-stage quantitative approach was applied. First, Data Envelopment Analysis with an input-oriented Variable Returns to Scale model was used to measure technical efficiency across ten local governments. Second, System Generalized Method of Moments estimation was employed to analyze the determinants of efficiency while addressing endogeneity and unobserved heterogeneity. The results show substantial variation in expenditure efficiency, with scores ranging from 0.48 to 1.00, indicating that greater fiscal resources do not automatically lead to efficient public spending. Government performance accountability has a positive and significant effect on expenditure efficiency, suggesting that systematic planning, monitoring, and evaluation encourage better resource allocation. In contrast, bureaucratic reform does not show a significant direct effect, implying that structural reforms may require a longer period to influence fiscal efficiency. The findings highlight the importance of strengthening performance accountability systems to improve local government expenditure efficiency.